دور القيادة الإدارية في تحسين الأداء الوظيفي دراسة حالة مصحة ابن حيان بالوادي - طليبة كوثر; باي منى (eloued of university جامعة الوادي, 2025)
" تهدف هذه الدراسة إلى الكشف عن العلاقة بين أبعاد القيادة الإدارية والأداء الوظيفي داخل المؤسسة، وذلك من خلال تحليل مدى تأثير الرؤية، الرسالة، الغايات، الأهداف، والقيم القيادية على أداء العاملين، واعتمدت الدراسة على المنهج الوصفي التحليلي لملاءمته لطبيعة الموضوع، حيث تم جمع البيانات وتصنيفها وتحليلها لفهم العلاقة بين المتغيرات وإعتمدت الدراسة التطبيقية على أداة الإستبيان عن طريق برنامج spss22، وأسفر اختبار الفرضيات عن النتائج التالية: حيث لم يُثبت وجود أثر دال للرؤية والرسالة القيادية على الأداء الوظيفي، ولم يظهر للأهداف القيادية أثر معنوي على الأداء، وفي المقابل أيضا ثبت وجود أثر ذي دلالة إحصائية لكل من الغايات والقيم القيادية على الأداء الوظيفي. وتبيّن في الأخير أن التأثير الأكبر على الأداء الوظيفي يعزى إلى الجوانب العملية والسلوكية المتمثلة في الغايات والقيم، مقارنة بالعناصر النظرية كالرؤية والرسالة، وعليه فإن تعزيز الأداء الوظيفي يتطلب تركيزًا أكبر على صياغة غايات واضحة وقيم تنظيمية محفزة تعكس واقع المؤسسة واحتياجات موظفيها. "This study aimed to explore the relationship between the dimensions of administrative leadership and job performance within an organization. This was achieved by analyzing the extent to which vision, mission, goals, objectives, and leadership values influence employee performance. The study began with a primary question: What is the extent to which the components of administrative leadership influence job performance? The study relied on a descriptive-analytical approach, given its suitability to the nature of the topic. Data was collected, classified, and analyzed to understand the relationship between variables. Hypothesis testing yielded the following results: No significant effect of leadership vision and mission on job performance was demonstrated, and leadership goals did not appear to have a significant effect on performance. Conversely, a statistically significant effect of both leadership goals and values on job performance was demonstrated. Finally, it was found that the greatest impact on job performance is attributed to the practical and behavioral aspects represented by goals and values, compared to theoretical elements such as vision and mission. Therefore, enhancing job performance requires a greater focus on formulating clear goals and motivating organizational values that reflect the reality of the organization and the needs of its employees.
ماستر علوم اقتصادية
Keywords: القيادة الإدارية; ا لأداء الوظيفي; المؤسسة; Administrative leadership - job performance - organization.